Rights and Liabilities of Scholars and Scholarship Authorities for Breach of Scholarship Agreements under the Contracts (Amendment) Act 1976 - Balan, Sujata (Journal of Malaysian and Comparative Law, 2019)
The purpose of this article is to examine and evaluate the rights and liabilities of the scholar and the scholarship authority and the remedies available to them in the event of a breach of a scholarship agreement. The scope of this article is confined to scholarship agreements regulated by the Contracts (Amendment) Act 1976 (hereafter referred to as "the Amendment Act"). As will be discussed at a later stage of this article, the Amendment Act regulates scholarship agreements made between a scholar and the Federal Government or State Government or a statutory authority or an approved educational institutiona under the Amendment Act. Hence, this article does not cover scholarship agreements made between private bodies and scholars as these scholarship agreements do not come within the ambit of the Amendment Act. This article is divided into five parts. The introduction is contained in Part I. Part II of this article discusses the position of the law on scholarship agreements prior to the passing of the Amendment Act. Part II examines the new scheme of the law under the Amendment Act and some of its vital provisions. Part IV deals with specific provisions of the Amendment Act which relate to the rights and liabilities of and remedies available to the contracting parties. Part V examines how the courts have interpreted and applied these provisions. Part VI then considers whether the present law should undergo reform. Finally, Part VI contains the writer's concluding remarks.